2015
DOI: 10.1021/es505121p
|View full text |Cite
|
Sign up to set email alerts
|

Consumption-Weighted Life Cycle Assessment of a Consumer Electronic Product Community

Abstract: A new approach for quantifying the net environmental impact of a "community" of interrelated products is demonstrated for consumer electronics owned by an average U.S. household over a 15-year period (1992-2007). This consumption-weighted life cycle assessment (LCA) methodology accounts for both product consumption (number of products per household) and impact (cumulative energy demand (MJ) and greenhouse gas emissions (MT CO2 eq) per product), analyzed using a hybrid LCA framework. Despite efficiency improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 38 publications
(79 reference statements)
0
41
0
Order By: Relevance
“…Given the rapid expansion of the ownership of EEE, little attention has been paid to sharing or other more intensive use strategies. It has, however, been observed that the integration of functions into smart-phones and other multi-use devices can contribute to reducing the number of devices owned by an individual and thus reduce the material and energy demand caused by the production (and operation) of EEE [17,194]. Given these recent trends towards smaller, more integrated products, there has been a shift in the demand for material classes from reduced use of bulk material quantities, but increased quantities of active components such as integrated circuits.…”
Section: More Intensive Usementioning
confidence: 99%
See 1 more Smart Citation
“…Given the rapid expansion of the ownership of EEE, little attention has been paid to sharing or other more intensive use strategies. It has, however, been observed that the integration of functions into smart-phones and other multi-use devices can contribute to reducing the number of devices owned by an individual and thus reduce the material and energy demand caused by the production (and operation) of EEE [17,194]. Given these recent trends towards smaller, more integrated products, there has been a shift in the demand for material classes from reduced use of bulk material quantities, but increased quantities of active components such as integrated circuits.…”
Section: More Intensive Usementioning
confidence: 99%
“…More intensive use [4]: less product to provide the same service, e.g. through a more space-efficient design of buildings or multifunctionality of gadgets [17], or use of a product at a higher utilization rate, e.g. through sharing.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of consumer electronics, this rebound effect (or Jevons paradox) has been observed in both an increased product ownership leading to greater cumulative impact (Ryen et al. , ) or in an increased product performance, resulting in no net material reduction (Kasulaitis et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, although the efficiency of consumer electronics has improved over the last two decades, the total growth in ownership and usage has increased the corresponding environmental impacts (Ryen et al. ). Product usage, and therefore the corresponding electricity consumption, is a function of consumer behavior, which is highly variable.…”
Section: Introductionmentioning
confidence: 99%